1990
DOI: 10.1103/physrevb.41.799
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of positron-annihilation-induced Auger-electron spectroscopy to the top surface layer

Abstract: We present the 6rst study of positron-annihilation-induced Auger-electron emission from a well defined overlayer-metal system. A 0.5 monolayer of S on Cu(110) produced a fourfold reduction in the positron induced Cu M2, 3VV Auger peak. The attenuation is accounted for by theoretical calculations indicating that the positron surface state is displaced away from the Cu surface by the S overlayer, decreasing the annihilation rate of positrons with Cu core electrons.Conventional methods of Auger-electron spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 13 publications
2
16
2
Order By: Relevance
“…PAES allows experiments with extremely high surface sensitivity, since most of the implanted positrons are trapped in surface bound states and annihilate with electrons in the topmost atomic layer [4,5]. It was demonstrated that 95% of the Auger-signal stemmed from the uppermost atomic layer [6].…”
Section: Introductionmentioning
confidence: 98%
“…PAES allows experiments with extremely high surface sensitivity, since most of the implanted positrons are trapped in surface bound states and annihilate with electrons in the topmost atomic layer [4,5]. It was demonstrated that 95% of the Auger-signal stemmed from the uppermost atomic layer [6].…”
Section: Introductionmentioning
confidence: 98%
“…[14][15][16][17] Recently the nature and location of positron bound states at metal surfaces, both clean and adsorbate-covered, have become the subject of experimental studies using positronannihilation-induced Auger-electron spectroscopy ͑PAES͒. [18][19][20][21][22][23][24][25] In PAES experiments most of the low-energy positrons, implanted into the sample under study, diffuse back to the vacuum-solid interface where on the order of half are trapped into a surface state. 18,25 A certain fraction of the surface trapped positrons annihilates with neighboring corelevel electrons, creating core-hole excitations that give rise to Auger-electron emission.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PAES is much more surface sensitive than AES, since most of the implanted positrons are trapped at the surface bound states and annihilate with electrons in the topmost atomic layer [2,3].…”
mentioning
confidence: 99%